The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1038/pj.2009.326
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state polymerization of conjugated hexayne derivatives with different end groups

Abstract: Three hexayne derivatives with different end groups-that is, 10,12,14,16,18,20-triacontahexayne-1,30-diol (1) and its diphenylurethane (2) and diphenylester (3)-were synthesized, and their solid-state polymerization behaviors were investigated. All three monomers were thermally polymerizable. Polymers from 1 and 2 showed an absorption maximum at about 730 nm, indicating that linear polydiacetylenes (PDAs) with octatetraynyl substituents were synthesized. However, broad absorption bands in the near-infrared re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
(41 reference statements)
3
7
0
Order By: Relevance
“…Such a red shift was also observed in a PDA-ladder system prepared from hexaacetylenes. 23,27,43 The red shift originating in the expansion of p-system was also predicted theoretically. 44 Although an excitonic transition was usually observed in PDAs around 2 eV, 41,42 the lowest absorption band was assigned to an interband transition.…”
Section: Resultssupporting
confidence: 56%
“…Such a red shift was also observed in a PDA-ladder system prepared from hexaacetylenes. 23,27,43 The red shift originating in the expansion of p-system was also predicted theoretically. 44 Although an excitonic transition was usually observed in PDAs around 2 eV, 41,42 the lowest absorption band was assigned to an interband transition.…”
Section: Resultssupporting
confidence: 56%
“…It is worth noting that the shapes of the electronic spectra of the hosted mitoxantrone molecules are similar to those found in diluted aqueous solutions, in which there are no stacking interactions . Thus, it can be concluded that the adsorption of mitoxantrone molecules into the 1D MOF’s pores involves the loss of π–π-stacking interactions. , …”
Section: Resultssupporting
confidence: 58%
“…81 Thus, it can be concluded that the adsorption of mitoxantrone molecules into the 1D MOF's pores involves the loss of π−π-stacking interactions. 82,83 Regarding the mitoxantrone delivery in SBF (pH ∼ 7.4) from the loaded ZnBDP_X@mitoxantrone matrixes, the tendency of mitoxantrone to precipitate at pH = 6−8, 84 which hampers here any accurate determination of the delivery process in this medium, should be pointed out. Further investigations are being made in order to study the complex delivery of mitoxantrone from the ZnBDP_X matrixes.…”
Section: Colloidal Stability Of Znbdp_oh Under Relevant Physiological...mentioning
confidence: 99%
“…Conjugated oligoynes or polyynes constitute a class of quasi-one-dimensional conjugated carbon chains and have been extensively investigated as versatile scaffoldings for functional carbon-rich materials, owing to their rich optoelectronic and electromagnetic properties and unique solid-state reactivities. For instance, the nonlinear optical susceptibilities of oligoynes were found to increase exponentially with increasing number of acetylenic repeat units, , while topochemical polymerization of oligoynes tended to result in highly conjugated polymer networks , and ordered carbon-based nanomaterials. Moreover, the “wire-like” sp carbon chains (spCCs) of conjugated oligoynes or polyynes are the substructures of an intriguing carbon allotrope−carbyne, , while debates over the nature of electronic delocalization in spCCs have galvanized both experimental and theoretical investigations. In particular, synthetic endeavors aiming at extension and functionalization of conjugated oligoynes have been actively undertaken in recent years in order to realize suitable models for unraveling the mystical characteristics of carbyne and related polyyne materials. …”
Section: Introductionmentioning
confidence: 99%